Influencing Factors of Organizational Citizenship Behavior (OCB) in Middle School/ MTS Boarding School Teachers - Supriyati, Supriyati; Sutarto, Joko; Yanto, Heri (Educational Management, 2020)
This aims of the study are determining, testing and analyzing the influence of school principal leadership and work environment on Organizational Citizenship Behavior (OCB) teachers by using organizational culture as an intervening variable in SMP / MTS Boarding School teachers which spreading across in Banyumas Residency . The respondents of this study were 170 SMP / MTS Boarding School teachers which spreading across in Banyumas Residency. The way to take the sample are using proportional random sampling and analysis techniques using path on analysis ( path analysis ) . The results showed that: 1) There is an influence of the principal's leadership on organizational culture. 2) There is an influence of the work environment on organizational culture. 3) There is an influence of the principal's leadership on the Organizational Citizenship Behavior (OCB) . 4) There is an influence of the work environment on Organizational Citizenship Behavior (OCB) . 5) There is an influence of culture on Organizational Citizenship Behavior (OCB) . 6) There is an influence of the principal's leadership on Organizational Citizenship Behavior (OCB) through organizational culture. 7) There is an influence of the work environment on Organizational Citizenship Behavior (OCB) through organizational culture. Based on these findings, Organizational Citizenship Behavior (OCB) can be improved through the improvement in leadership of the school principal, work environment and organizational culture.